Antitrust law and the promotion of democracy and economic growth - Niels Petersen (Max Planck Institute for Research on Collective Goods, 2011)
There is a considerable debate in the legal literature about the purpose of antitrust institutions. Some argue that antitrust law merely serves the purpose of economic growth, while others have a broader perspective on the function of antitrust, maintaining that the prevention of economic concentration is an important means to promote democratization and democratic stability. This contribution seeks to test the empirical assumptions of this normative debate. Using panel data of 154 states from 1960 to 2007, it analyzes whether antitrust law actually has a positive effect on democracy and economic growth. The paper finds that antitrust law has a strongly positive effect on the level of GDP per capita and economic growth. However, there is no significant positive effect on the level of democracy. It is suggested that these results might be due to the current structure of existing antitrust laws, which are designed to promote economic efficiency rather than to prevent economic concentration.
Keywords: 330; Kartellrecht; Wirtschaftswachstum; Volkseinkommen; Demokratie; Schätzung; Welt